Left Side Appendicitis with Midgut Malrotation in an Adult - Birnbaum, David Jérémie (Medknow Publications & Media Pvt Ltd, 2013)
Midgut malrotation (MMR) is a congenital anomaly referring to either nonrotation or incomplete rotation of the primitive intestinal loop around the axis of the superior mesenteric artery during fetal development. Adult MMR is rare and majority of MMR in adults remains asymptomatic throughout life. The increasing use of diagnostic imaging for acute abdominal pain will lead to more incidental recognitions of MMR. Up to now, surgical treatment has been guided by the experience from pediatric surgery, and Ladd's procedure has been the treatment of choice in adults with MMR. However, a major dilemma arises when patients are essentially asymptomatic and incidentally diagnosed with MMR during another abdominal affection like acute appendicitis. The surgeon has to decide whether it is necessary to also treat the MMR. Here, we report a rare case of a 37-year-old patient with acute left side appendicitis in association with asymptomatic MMR. We discuss whether correction of the asymptomatic malrotation was indicated.